Spending Review pada APBD Kota Bandung di Masa Pandemi Covid-19 - Putra, Sugih Sutrisno; Suryana, Novia Aisyah (JPAK : Jurnal Pendidikan Akuntansi dan Keuangan, 2022)
AbstractEfficiency review is one of the methods of spending review, is something that the government must do, especially during the Covid-19 pandemic, which makes the government have to refocus and reallocate the budget on a fairly large scale. The Bandung City Government has been refocusing and reallocating the budget since the beginning of the pandemic, causing changes to the structure of the updated Regional Revenue and Expenditure Budget (APBD) of the year 2020. The research uses a descriptive method with a qualitative approach and the data analysis technique uses in this study is the data analysis method according to Miles and Huberman (1994) which includes the process od data reduction, data display, and conclusion drawing/verification. The results show that in the period of two fiscal years, namely 2019-2020, there was a deviation between the budget allocation and the real needs of the Bandung City Government. However, when viewed in terms of benchmarking analysis, the performance of the Bandung City Government is quite good.